Identifikasi Jenis dan Populasi Jamur Tanah pada Habitat Tanaman Kubis (Brassica oleracea L.) Sehat dan Sakit Akar Gada pada Sentra Produksi Kubis di Kecamatan Baturiti Tabanan - INDRAYOGA, PANDE MADE; SUDARMA, I MADE; PUSPAWATI, NI MADE (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2013)
ABSTRACT Identify Types and Population of Soil Fungi on Cabbage ( Brassicae oleracea L.) Health and Infected Habitat of Clubroot in Baturiti District, Tabanan Cabbage is a vegetable that potential to be developed, because a lot of people favored this vegetable. Cabbage crop production level is often affected by the attacks of pathogen Plasmodiophora brassicae that causes swelling at the root. This disease can reduce the production of cabbage plants up to 80%. The aim of this research is to investigate species variety and soil fungi population on healthy cabbage plant’s rizosphere (suppressive) and diseased cabbage or diseased sympton (conducive) of club root ( Plasmodiophora brassicae ), and also soil fungi which more dominant on isolation result of soil fungi, to investigate the relation of soil’s physico-chemistry nature with soil fungi population, and to investigate fungi species that able to antagonize P. Brassicae fungi. This research used 3 samples of soil which taken from both healthy and club root diseased cabbage plant’s rizosphere, where the soil’s sample taken from 3 locations, that are: Pekarangan, Baturiti Kaja, and Pacung. The result of this research shown that there are 17 species of soil fungi found on the sample of suppressive and conducivesoil in three locations, where the population of Fusarium sp. fungi becomes dominant soil fungi. This research also shown that on the relation between soil physico-chemistry nature and soil fungi population was not positively correlated, and species fungi of Trichoderma sp. is able to inhibit the growth of P. Brassicae fungi. Keywords: Cabbage plant, Plasmodiophorabrassicae, species and population of soil fungi, suppressive and conducive soil.
Keywords: Cabbage plant; Plasmodiophorabrassicae; species and population of soil fungi; suppressive and conducive soil